2022
DOI: 10.3389/fragi.2022.866718
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Senescence and Ageing: Mechanisms and Interventions

Abstract: The influence of the activation of a cellular phenotype termed senescence and it’s importance in ageing and age-related diseases is becoming more and more evident. In fact, there is a huge effort to tackle these diseases via therapeutic drugs targeting senescent cells named senolytics. However, a clearer understanding of how senescence is activated and the influence it has on specific cellular types and tissues is needed. Here, we describe general triggers and characteristics of senescence. In addition, we des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 84 publications
(111 reference statements)
0
40
0
Order By: Relevance
“…In addition, cellular senescence can be triggered by various intrinsic and extrinsic stimuli, as well as developmental signals, whereby the types of senescence mainly include replicative senescence (RS), oncogene-induced senescence (OIS), stress-induced premature senescence (SIPS), and developmental senescence (DS) (Mylonas & O'Loghlen, 2022;Zhou et al, 2020). In this study, GA-D showed significant protective effects against MSCs senescence induced by In conclusion, our results demonstrated that GA-D protects hAMSCs against H 2 O 2 -induced senescence by targeting 14-3-3ε to activate the CaM/CaMKII and Nrf2/HO-1/NQO1 signaling pathways (Figure S7).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cellular senescence can be triggered by various intrinsic and extrinsic stimuli, as well as developmental signals, whereby the types of senescence mainly include replicative senescence (RS), oncogene-induced senescence (OIS), stress-induced premature senescence (SIPS), and developmental senescence (DS) (Mylonas & O'Loghlen, 2022;Zhou et al, 2020). In this study, GA-D showed significant protective effects against MSCs senescence induced by In conclusion, our results demonstrated that GA-D protects hAMSCs against H 2 O 2 -induced senescence by targeting 14-3-3ε to activate the CaM/CaMKII and Nrf2/HO-1/NQO1 signaling pathways (Figure S7).…”
Section: Discussionmentioning
confidence: 99%
“…Aging is characterized by the accumulation of damage to macromolecules and cell architecture resulting in a progressive decrease in the function of tissue and organ due to nutrition, genetic and environmental factors, and lifestyle [ 28 ]. The accumulation of these damaged arrested cells was observed with the increase in age [ 29 ], and these senescent cells were noted to contribute to diseases that are related to aging, such as renal damage [ 30 ], alcoholic fatty liver disease [ 31 ], cerebrovascular disorders [ 32 ], diabetes [ 12 ], and Alzheimer's disease [ 33 ]. Cellular senescence is an inherent process that inhibits tumor progression, contributing to arresting the cells autonomously in the cell cycle and preventing further divisions.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulation of DNA in the cytoplasm serves as a potent danger signal that can activate an innate immunity cytosolic DNA sensing pathway, leading to proinflammatory responses. In fact, SASP is associated with various growth-regulatory factors, cytokines, and chemokines (Krtolica et al, 2001; Mylonas & O’Loghlen, 2022). We found a significant increase in secreted soluble factors such as IL-1α, IL-6, and MIP-1α in aged mouse urines and tissues.…”
Section: Discussionmentioning
confidence: 99%